Effect of Surfactants on the Synthesis and Dissociation of Gas Hydrates; Fire; Vol. 7, iss. 7 - Misyura S. Ya. Sergey Yakovlevich; Morozov V. S. Vladimir Sergeevich; Strizhak P. A. Pavel Alexandrovich; Shlegel N. E. Nikita Evgenjevich; Donskoy I. G. Igor Gennadjevich (2024, 2024)
Title screen